Water Birth – Benefits, Risks, and Controversies - Julia Górny; Alicja Kapciak; Katarzyna Naja; Jakub Zwardoń; Artur Hawajski; Natalia Jankowska; Oliwia Kamieniecka; Adrianna Świerzyńska; Weronika Mazur; Natalia Pawelec (Quality in Sport)
Introduction: